2020
DOI: 10.1016/j.ijlp.2019.101506
|View full text |Cite
|
Sign up to set email alerts
|

Reasons behind the rising rate of involuntary admissions under the Mental Health Act (1983): Service use and cost impact

Abstract: There has been a significant rise in the use of the Mental Health Act (1983) in England over the last 10 years. This includes both health-based Place of Safety detentions and involuntary admissions to NHS mental health facilities. Although these trends should clearly inform the implementation of mental health care and legislation, there is currently little understanding of what caused these increased rates. We therefore sought to explore potential underlying reasons for the increase in involuntary admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The recent overhaul of the MHA 12 includes minimising detentions among Black people and other ethnic minorities which is likely to both improve patient experience 13 and also address the substantial costs to the NHS associated with being detained under section. 14 With regard to suicide, there are few large-scale studies on ethnicity to inform policy and practice; furthermore ethnicity is not routinely recorded on national death registrations in England and…”
Section: Introductionmentioning
confidence: 99%
“…The recent overhaul of the MHA 12 includes minimising detentions among Black people and other ethnic minorities which is likely to both improve patient experience 13 and also address the substantial costs to the NHS associated with being detained under section. 14 With regard to suicide, there are few large-scale studies on ethnicity to inform policy and practice; furthermore ethnicity is not routinely recorded on national death registrations in England and…”
Section: Introductionmentioning
confidence: 99%
“…32 An even more recent study has reported no significant association between in-patient bed numbers and detention rates in a multivariate model, for the period from 1999 to 2016. 42 Internationally, greater in-patient bed availability is associated with higher, not lower, rates of compulsory admissions. 1…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing, interpreting, and comparing our results, the interplay between patient characteristics, local mental health services peculiarities, and legal regulations must be considered. They regulate and determine the patients’ access to treatment and directly influence therapeutic interventions [6,15,60–62]. In Switzerland, the rate of compulsory admission orders is high compared to other countries, suggesting a relatively low threshold for their use [11,62].…”
Section: Discussionmentioning
confidence: 99%